Bilateral bullous keratopathy secondary to melting keratitis in a Suri alpaca (Vicugna pacos). Issue 4 (15th February 2018) - Guyonnet, Alexandre; Bourguet, Aurélie; Donzel, Elise; Bataille, Guillemette; Pascal, Quentin; Laloy, Eve; Boulouis, Henri‐Jean; Milleman, Yves; Chahory, Sabine
Key Clinical Message: An young alpaca was evaluated for bilateral progressive melting corneal ulcers and developped secondary bullous keratopathy during hospitalization. The tragic progression of melting ulcers in both eyes observed in our case leads us to recommend a rapid intensive medical therapy in young and debilitated alpacas presenting a corneal ulcer. Abstract : The tragic progression of melting ulcers in both eyes observed in our case leads us to recommend a rapid intensive medical therapy in young and debilitated alpacas presenting a corneal ulcer.